Where to retire : America's best & most affordable places - Howells, John, 1928-; Conroy, Teal (Guilford, Connecticut : GPP, 2015)
"Gives readers ... snapshots of life in hundreds of the most affordable, comfortable, and stimulating places to retire in the United States"--
Includes bibliographical references and index.
Keywords: Retirement, Places of -- United States; Quality of life -- United States; Social indicators -- United States; TRAVEL -- Special Interest -- Senior; BUSINESS & ECONOMICS -- Personal Finance -- Retirement Planning; Quality of life; Retirement, Places of; Social indicators; United States